Assessment of components of essential oils for antimicrobial activity in the dairy food matrix - G, Manju; Chand Ram Grover (Indian Journal of Dairy Science, 2023)
Essential oils as a whole have been widely investigated for their antimicrobial properties against spoilage microorganisms and pathogens. However limited information is available about the inhibitory activities of components of EO in foods and more specifically in dairy food matrices. The widespread components of common EOs were evaluated for their antibacterial activity in media and skim milk. Amongst the components, trans-cinnamaldehyde and eugenol were the most effective with minimum bactericidal concentrations of 4 mg/ml and 12 mg/ml, respectively in milk. The trans-cinnamaldehyde had the lowest MBC of 10 mg/g in paneer slurry against L. monocytogenes and E. coli O157:H7. The microbial load in paneer made from EO added to milk (1%) significantly inhibited microbial growth during storage. In the dairy spread, trans-cinnamaldehyde and eugenol were effective in inhibiting TBC, coliform, and yeast & mold count at 0.25 mg/ml without affecting sensory properties.